2012
DOI: 10.1016/j.ijpsycho.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the future: From implicit learning to consolidation

Abstract: Sequence learning can be differentiated according to phases (rapid and slower), modalities (perceptual and motor), and whether or not it is conscious (implicit and explicit). Implicit sequence learning occurs when information is acquired from an environment of complex stimuli without conscious access either to what was learned or to the fact that learning occurred. In everyday life, this learning mechanism is crucial for adapting to the environment and for predicting events unconsciously. Implicit sequence lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 116 publications
(199 reference statements)
6
52
0
3
Order By: Relevance
“…Sequences can be learned in different ways: explicitly, e.g., in finger-opposition or finger-tapping paradigms (Korman et al, 2003; Doyon et al, 2009b; Friedman and Korman, 2012) or implicitly, e.g., in serial reaction time paradigms (Destrebecqz and Peigneux, 2005; Janacsek and Nemeth, 2012), depending on the intention or awareness during acquisition (Nissen and Bullemer, 1987; Hikosaka et al, 2002; Robertson, 2007). Both types of sequence learning depend on the amount of practice (Karni, 1996; Schmidt and Lee, 1999; Page and Norris, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences can be learned in different ways: explicitly, e.g., in finger-opposition or finger-tapping paradigms (Korman et al, 2003; Doyon et al, 2009b; Friedman and Korman, 2012) or implicitly, e.g., in serial reaction time paradigms (Destrebecqz and Peigneux, 2005; Janacsek and Nemeth, 2012), depending on the intention or awareness during acquisition (Nissen and Bullemer, 1987; Hikosaka et al, 2002; Robertson, 2007). Both types of sequence learning depend on the amount of practice (Karni, 1996; Schmidt and Lee, 1999; Page and Norris, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the time course of learning sequences of finger movements on a basic behavioral level (number of sequences performed, error rate) as well as neural correlates using neuroimaging (Karni et al, 1995; Hikosaka et al, 2002; Keele et al, 2003; Korman et al, 2003; Luft and Buitrago, 2005; Janacsek and Nemeth, 2012). A few hours after practice, skills are processed, changed and strengthened in memory (Karni and Sagi, 1993; Karni et al, 1995), a phenomenon commonly described as procedural memory “consolidation” (Karni and Sagi, 1993; Walker, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The issue could be explained by previous studies in which it is indicated that the lack of practice within hours or days stabilizes memory traces created in the acquisition period and makes neural substrates resistant. [22,23] This concept, called memory consolidation, can lead to increased resistance to interference or even an improvement in performance after a no-practice period. [23] In fact, motor skills are completed by two different processes.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] This concept, called memory consolidation, can lead to increased resistance to interference or even an improvement in performance after a no-practice period. [23] In fact, motor skills are completed by two different processes. Skill can develop during practice (acquisition) sessions called on-line learning, and also develop off-line -between practice sessions or during a no-practice period 24 .…”
Section: Discussionmentioning
confidence: 99%
“…So, how do we estimate what will be next (and exactly when), given the presence? Depending on the situation or experimental task, either formal transition rules (Janacsek & Nemeth, 2012), naive physics (Zago & Lacquaniti, 2005), or probability distributions (Fiser, Berkes, Orbán, & Lengyel, 2010) can serve to tune expectation for upcoming stimuli. However, a straightforward way to classify prediction is by its memory base.…”
Section: Predicting Upcoming Statesmentioning
confidence: 99%